Neural alterations in working memory of mild-moderate TBI: An fMRI study in Malaysia - Wen Jia Chai; Aini Ismafairus Abd Hamid; Hazim Omar; Muhammad Riddha Abdul Rahman; Diana Noma Fitzrol; Zamzuri Idris; Abdul Rahman Izaini Ghani; Wan Nor Azlen Wan Mohamad; Faiz Mustafar; Muhammad Hafiz Hanafi; Regunath Kandasamy; Mohd Zaid Abdullah; et al. (WILEY, 2024)
Indexed by WOS/Scopus/ERA